THE INFLUENCE OF AL-KASBU ON SA’ADATUL UMMAL IN ISLAMIC BANKS IN EAST KALIMANTAN PROVINCE - Wati, Maria (STIT Ibnu Rusyd Tanah Grogot, 2024)
The purpose of this study is to analyze the influence of al-kasbu on sa'adatul ummal in Islamic banks in East Kalimantan Province. This study uses a quantitative and qualitative approach, which is useful for descriptively explaining the existence and role of a research object or research variable on other research variables, by statistically analyzing the causal relationship between research variables. The results reveal that Al-Kasbu has a significant positive effect on Sa'adatul Ummal. The higher the al-Kasbu, the higher the sa'adatul ummal. The ability to manage wealth/assets and the strong next generation of families from Islamic banks in East Kalimantan Province over the last 5 years, from 2008 to 2012, has also increased annually. Al-Kasbu has been carried out properly and correctly by employees at Islamic banks in East Kalimantan Province in accordance with the meaning contained in al-Qur'an surah (9) at-Taubah verse 105, although it is not yet kaffah because the quality of work is still not optimal, as indicated by the lowest average perception score of respondents. Al-Kasbu, which is employee performance with indicators: achievement, speed/accuracy, service, quality of work, increasing the amount of Zakat Infaq Shadaqah (ZIS), increasing sunnah worship, discipline, and efficiency, has a significant positive effect on Sa'adatul Ummal. This means that the higher the al-Kasbu, the more Sa'adatul Ummal will increase through indicators of maintaining religion, soul, intellect, wealth, and offspring. This ultimately increases the overall Sa'adatul Ummal for Islamic bank employees in East Kalimantan Province.